The Impact of IFAD’s Involvement as an Inter-Governmental Organisation in the Livelihood of Moroccan Family-Farms - Gwladys Nicimbikije; Elisabeth Dewi (Parahyangan Center for International Studies, 2021)
Family farming exists overall and each has its own unicity in term of managing the farm operations, farm size, productivity, socio-economic conditions, local knowledge and geographical location besides the externalities such as depletion of resources exacerbated by the climate change. Hence, the following question drove the authors: “to what extent of involvement are intergovernmental organization concerned with farmers’ livelihood in Morocco?” Therefore, this research purpose outlines the role of family farming and their characteristics; challenges of farming livelihood and productivity in Morocco; and IFAD’s support for inclusive rural transformation. The authors hold view that family farming with higher on-farm innovative inputs of processing activities can expect increased yield. The findings revealed that IFAD’s global governance endowed by modern corporation, -corporate governance for instance, - enables participation of rural beneficiaries in their projects thus increases their self-management onto (environmental) natural resources and sustainability. Skills, training, innovation and technologies allow them to diversify and intensify their agricultural holdings hence access to new markets and cope with the ecological risks though there is limitation with the innovation and services extension.